MSB-First Interval-Bounded Variable-Precision RealTime Arithmetic Unit - Yusrila Y. Kerlooza; Yudi S. Gondokaryono; Agus Mulyana (Journal of ICT Research and Applications, 2010)
This paper presents a paradigm of real-time processing on the lowest level of computing systems: the arithmetic unit. The arithmetic unit based on this principle containing addition, subtraction, multiplication and division operations is  described.  The  development  of  the  computation  model  is  based  on  the  Soft Computing and the Imprecise Computation paradigms, combined with the MSBFirst  and  the  Interval  Arithmetic  techniques.  Those  paradigms  and  techniques give  the  arithmetic  unit  design  the  ability  to  compute  with  precisions  as  a function  of time available or accuracy needed. The predictability of processing time and result's accuracy are obtained by means of processing granularity of k bits and by  using look-up tables. We present an evaluation of  the operation in time  delay  and  computation  accuracy  that  shows  significant  performance improvement over conventional arithmetic unit architecture, that is,  the ability to produce  intermediate-result  during  execution  time,  to  give  certainty  in computation  accuracy  even  before  the  process  finish  time  by  providing  two intermediate-results,  which  act  as  the  lower  and  upper  bound  of  the  real  and complete computation result, and finally, gain high computation accuracy from the early time of the execution process.